Computational modelling studies of titanium TiN (N = 2-32) nanoclusters - Phaahla, Tshegofatso Michael (My University, 2022)
Transition metal nanoclusters have attracted a significant attention in both theoretical and experimental studies due to their unique properties such as structural, electronic and magnetic. These properties are distinct, size dependent and ranges between those of bulk and single-particle species. Some of the systems sizes have been experimentally synthesized, which enables direct theory-experiment comparison. Other clusters that have been examined theoretically are of interest as models of larger systems. Often, the size dependence of their HOMO-LUMO (H-L) gap, optical properties, magnetic properties, etc., is of interest. In this study, we have performed a genetic algorithm search on the tight-binding interatomic potential energy surface (PES) for small TiN (N = 2–32) clusters. Lowest energy candidate clusters were further refined using density functional theory (DFT) calculations with the PBEsol exchange-correlation functional and evaluated with the PBEsol0 hybrid functional. The resulting clusters were analysed in terms of their structural features, growth mechanism and surface area. The results suggest a growth mechanism that is based on forming coordination centres by interpenetrating icosahedra, icositetrahedra and Frank–Kasper polyhedra. We identified centres of coordination, which act as centres of bulk nucleation in medium-sized clusters and determine the morphological features of the cluster. Molecular dynamics simulations were performed in order to investigate the impact of thermal agitation on the TiN (N = 7, 13, 17, 32, 57, 80 and 89). The calculations were carried out at 300 – 2400 K. The interatomic interactions for vacuum and inert gas environment were modelled using Gupta and Leonard-Jones potentials as implemented within the classical molecular dynamics simulation software DL_POLY. The total potential energy, radial distribution functions (RDF), diffusion coefficient, mean square displacement and density profiles were examined to study the structural changes as a function of temperature. The TiN (N = 7, 17, 32, 57, 80 and 89) nanoclusters exhibit lower temperature structural transitions, whereas Ti13 nanocluster displayed melting-like structural transitions above the Ti bulk melting point. These transitions are dependent on the composition of the nanocluster. The icosahedron, two interpenetrating icosahedron and pentagonal bi-pyramid were found to be the most dominant building block geometries. The phase transitions from solid to liquid have been identified by a simple jump in the total potential energy curve, with the predicted melting temperature near that observed. As expected, the RDF’s and density profile peaks decrease with increasing temperature. The inert gas environment was found to exhibits features that are associated with the melting of nanoclusters below bulk Ti melting point. We further explored the reactivity and electronic properties of the Ti nanoclusters when they are modified by different impurity elements. Structures and electronic properties of TiN-1M (N = 2 – 16) nanoclusters have been investigated using the density functional theory method with the PBEsol exchange-correlation functional. In order to locate the stable TiN-1M (M = Pt, Ir, Pd and Ni) bimetallic clusters, the Pt atom was doped in all the coordinated atoms of TiN (N = 2-16) clusters. Then, the same position with the lowest energy was used to investigate the stability and electronic properties for other impurities. The results suggested Iridium as the most energetically favoured dopant as revealed by the lowest binding energy. However, the relative stability and dissociation energy revealed Ti12Pt as the most stable isomer. Furthermore, H-L gaps revealed the reduction of the quantum confinement, reactive and non-reactive isomers as the cluster size N increases. The H-L and density of state revealed no correlation with the stability measure quantities (relative stability and dissociation energy).
Thesis (Ph.D. (Physics)) -- University of Limpopo, 2022
Keywords: Titanium; Transition metal nanoclusters; Titanium nanostructures; Titanium; Titanium dioxide films -- Electric properties; Titanium dioxide.